ATP and ACh Evoked Calcium Transients in the Neonatal Mouse Cochlear and Vestibular Sensory Epithelia - Rabbitt, Richard D.; Holman, Holly A. (Frontiers in Neuroscience, 2021)
Hair cells in the mammalian inner ear sensory epithelia are surrounded by supporting cells which are essential for function of cochlear and vestibular systems. In mice, support cells exhibit spontaneous intracellular Ca2+ transients in both auditory and vestibular organs during the first postnatal week before the onset of hearing. We recorded long lasting (>200 ms) Ca2+ transients in cochlear and vestibular support cells in neonatal mice using the genetic calcium indicator GCaMP5. Both cochlear and vestibular support cells exhibited spontaneous intracellular Ca2+ transients (GCaMP5 ΔF/F), in some cases propagating as waves from the apical (endolymph facing) to the basolateral surface with a speed of ∼25 μm per second, consistent with inositol trisphosphate dependent calcium induced calcium release (CICR). Acetylcholine evoked Ca2+ transients were observed in both inner border cells in the cochlea and vestibular support cells, with a larger change in GCaMP5 fluorescence in the vestibular support cells. Adenosine triphosphate evoked robust Ca2+ transients predominantly in the cochlear support cells that included Hensen’s cells, Deiters’ cells, inner hair cells, inner phalangeal cells and inner border cells. A Ca2+ event initiated in one inner border cells propagated in some instances longitudinally to neighboring inner border cells with an intercellular speed of ∼2 μm per second, and decayed after propagating along ∼3 cells. Similar intercellular propagation was not observed in the radial direction from inner border cell to inner sulcus cells, and was not observed between adjacent vestibular support cells.